THE EFFECT OF OKRA DECOCTION ON BLOOD SUGAR AND BODY WEIGHT IN DIABETIC CLIENTS - Satria Eureka Nurseskasatmata; Idola Perdana Sulistyoning Suharto (UPT Penerbitan Universitas Jember, 2020)
Background: Unstable blood sugar levels make people with diabetes more at risk when infected with Covid-19. Type 2 DM clients faced problems that can minimize if the client has sufficient knowledge and ability to control their disease, namely by doing selfies diabetes care. Okra plant (Abelmoschus esculantus) is associated with α-glucosidase, which has an antidiabetic effect on slowing the digestion of carbohydrates to delay the postprandial increase in blood glucose. Objective: To determine the impact of okra decoction on blood sugar and body weight. Methods: This study was a pre experimental study with a pre-post test one group design. The variables in this study were: the independent variable was vegetable okra stew (Abelmoschus esculentus), and the dependent variable was the level of blood sugar and body weight. The research subjects were 17 people selected by purposive sampling aged 40-71 years. The research subjects received 30 grams of okra stew per day at breakfast between 7-9 am for seven days and carried out blood sugar checks and body weight measurements. Result: the paired t-test statistical test on okra stew on blood sugar obtained p-value = 0.153), while the p-value = 0.000 for body weight, Conclusion: There was no significant difference between the administration of okra stew on blood sugar and there was a significant difference between the okra stew and body weight. It was expected that nurses could promote okra vegetables as complementary therapy in controlling blood sugar in diabetic patients by paying attention to diet, activity, and treatment. Key words: Okra, Blood Sugar, Body Weight, Diabetes Mellitus